Factors associated with total satisfaction with food-related life among elderly in Rumah Seri Kenangan, Selangor - Mohd Shahrin, Fatin Izzaty; Ahmad Zaimi, Noraida (Community Health Society Malaysia, 2018)
Background: There are various factors that may alter elderly relationship with food as they get older and eventually their satisfaction with food-related life (SWFL). Materials and Methods: A cross-sectional study was conducted to determine the associations between SWFL and socio-demographic factors, dietary intake, food access and malnutrition risk among elderly in Rumah Seri Kenangan. Socio-demographic, Mini- Nutritional Assessment (MNA), Experiences of food access (Naithani et al., 2009) and SWFL (Grunert et al., 2007) were assessed using sets of questionnaires. Dietary intake and anthropometric measurements were assessed using forms. All statistical analysis was performed using IBM SPSS version 21. Result: A total of 57 elderly were participated in this study where 47% of them were male and 53% were female. 40.4% of the subjects were at risk of malnutrition and 12.3% was malnourished. Male subjects consumed significantly higher in total energy and protein intake than female (p=0.008 and 0.034 respectively). However, 89.5% of subjects did not achieve for both recommended energy and protein intake of RNI. Experience with food access showed that majority of subjects had greater difficulty with physical barrier domain of food access (p=0.086) and the mean total score of each items in SWFL of 4.91 which indicated that elderly was somewhat agree with their SWFL. However, socio-demographic backgrounds, dietary intake, risk of malnutrition and food access were not associated with total SWFL Conclusion: Majority of subjects experienced difficulties in physical barrier domain and quite satisfied with their food-related life. Thus, improvement in the nutritional status can be achieved by providing adequate nutrition and enhancing food availability and accessibility to elderly in care homes.